2020
DOI: 10.5430/jnep.v10n10p61
|View full text |Cite
|
Sign up to set email alerts
|

Operationalization of bandura’s social learning theory to guide interprofessional simulation

Abstract: Background and objective: In the clinical setting, health care professionals are expected to work in teams, yet, there is limited academic exposure to other allied health students and little preparation is done in traditional classrooms to practice with other allied health students. As health professionals work in an environment influenced by social interaction, interprofessional simulation (IPS) instruction may lack necessary frameworks that support professional practice. To promote collaborative lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The level of difficulty is adjusted to the stages of learning and the learning objectives to be achieved so that in each meeting, the level of difficulty of the materials or learning materials is different. As mentioned by Stanley, the factors that influence attention are first; clarity, involvement of feelings, level of complexity, prevalence and value of the function of the material being modeled, second; observer characteristics such as sensory abilities, interests, perceptions, and prior reinforcement (Stanley et al, 2020).…”
Section: Observementioning
confidence: 99%
See 1 more Smart Citation
“…The level of difficulty is adjusted to the stages of learning and the learning objectives to be achieved so that in each meeting, the level of difficulty of the materials or learning materials is different. As mentioned by Stanley, the factors that influence attention are first; clarity, involvement of feelings, level of complexity, prevalence and value of the function of the material being modeled, second; observer characteristics such as sensory abilities, interests, perceptions, and prior reinforcement (Stanley et al, 2020).…”
Section: Observementioning
confidence: 99%
“…This study found that learning Arabic using Albert Bandura's theory was dominated by hiwār material, imitation of idioms, habituation, and did not teach qawā'id separately. Third, research conducted by Silahudun (Silahudun, 2020) entitled "Evaluation of Arabic Learning in Applied Albert Bandura's Social Cognitive Theory." The research method used is the descriptive analysis method.…”
Section: Introductionmentioning
confidence: 99%